Local principle of punishment of imprisonment and humane treatment of prisoners - Рудник, Віктор Іванович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
This article investigates the problem of reforming the basis penitentiary system and transform it into the penitentiary system of the European type, including local application of the principle of punishment in the form of deprivation of liberty (imprisonment) of the local prison and penitentiary system. The author stresses the improvement of conditions of detention of prisoners with humane treatment, maintaining social ties. Proposes amendments to the criminal and criminal-executive legistation, justified the need for penal code and the law of Ukraine "On the penitentiary service".